Fibrinogen/Albumin Ratio as a Promising Marker for Predicting Survival in Pancreatic Neuroendocrine Neoplasms - Deng, Shengming (Cancer Manag Res, 2021)
BACKGROUND: The fibrinogen/albumin ratio (FAR) has been widely reported to be a possible biomarker for predicting prognosis in several types of tumors, but the prognostic value of the FAR in pancreatic neuroendocrine neoplasms (Pan-NENs) has not been systematically studied. PATIENTS AND METHODS: In total, 324 patients with Pan-NENs were recruited. The patients were divided into 2 subgroups according to the FAR cutoff value, and clinicopathological characteristics of the 2 subgroups were compared. Overall survival (OS) was the primary endpoint, and progression-free survival (PFS) was the secondary endpoint. The prognostic value of the FAR was analyzed in univariate and multivariate analyses. RESULTS: The optimal cutoff value for the FAR was calculated to be 0.08 for OS. The patients with a FAR ≥0.08 had higher proportions of nonfunctioning tumors, Pan-NECs, grade 3 tumors, and stage IV tumors than those with a FAR <0.08. In the univariate analysis, a FAR ≥ 0.08 was associated with poor OS (hazard ratio (HR) = 2.37, P < 0.001) and PFS (HR = 2.37, P < 0.001). In the multivariate analysis, a FAR ≥0.08 was an independent risk factor for poor OS (HR = 4.70, P < 0.001) and PFS (HR = 1.80, P = 0.006). CONCLUSION: The pretreatment FAR, which includes fibrinogen and albumin, was a feasible and predictive biomarker for prognosis in patients with Pan-NENs. An elevated FAR, based on a cutoff value of 0.08, was an independent risk factor for poor OS and PFS.